Towards a new model of global health justice: the case of COVID-19 vaccines - Jecker, NS; Atuire, CA; Bull, SD (BMJ Publishing Group, 2022)
This paper questions an exclusively state-centred framing of global health justice and proposes a multilateral alternative. Using the distribution of COVID-19 vaccines to illustrate, we bring to light a broad range of global actors up and down the chain of vaccine development who contribute to global vaccine inequities. Section 1 (Background) presents an overview of moments in which diverse global actors, each with their own priorities and aims, shaped subsequent vaccine distribution. Section 2 (Collective action failures) characterises collective action failures at each phase of vaccine development that contributed to global vaccine disparities. It identifies as critical the task of establishing upstream strategies to coordinate collective action at multiple stages across a range of actors. Section 3 (A Multilateral model of global health governance) takes up this task, identifying a convergence of interests among a range of stakeholders and proposing ways to realise them. Appealing to a responsibility to protect (R2P), a doctrine developed in response to human rights atrocities during the 1990s, we show how to operationalise R2P through a principle of subsidiarity and present ethical arguments in support of this approach.